UN system engagement with NGOs, civil society, the private sector, and other actors : a compendium (UN New YorkUS, 2005)
Explains the broad system of United Nations offices, agencies, programmes and funds, and specialized agencies as well as UN treaty bodies. Provides information about the opportunities and procedures for the participation of non-governmental players in United Nations processes.
Keywords: UN